Administration of Immunoglobulins in SARS-CoV-2-Positive Patient Is Associated With Fast Clinical and Radiological Healing: Case Report - Carannante, Novella; Fiorentino, Giuseppe; Corcione, Antonio; Di Sarno, Raffaele; Spatarella, Micaela; Maturo, Nicola; Fragranza, Fiorentino; Di Micco, Pierpaolo (Frontiers in Medicine, 2020)
Polyclonal preparation of IgM as an adjuvant therapy has been reported as a relevant immunomodulant therapy in several infectious diseases, exhibiting, in most cases, improvement of the clinical course. No drug has demonstrated therapeutic efficacy for COVID-19. Immunomodulatory treatment with hydroxychloroquine and biologics as tocilizumab, in fact, has not proven to show satisfactory results in several reports. We therefore treated a selected patient with interstitial multifocal pneumonia, positive to COVID-19, with polyclonal preparation of immunoglobulins as an adjuvant therapy, obtaining in few days clinical remission and improvements in radiological findings. Based on this case report, we suggest that clinical trials are conducted to test the efficacy and safety of polyclonal immunoglobulins for adjunctive therapy of COVID-19.